ANALISA PENAMBAHAN GETAH DAMAR BATU (AGATHIS ALBA) PADA CAMPURAN ASPHALT CONCRETE-BINDER COURSE (AC-BC) - Tri Sefrus (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2013)
Research on the analysis of the resin stone resin on the concrete asphalt-binder course mixture (AC-BC) is motivated by resin vibration with asphalt, ie high viscosity and strong bonding power among particles and resin content in resin gum. Therefore, it is necessary to find out the effect of sap damar stone 0%; 1.5%; 2.5% and 3.5% of asphalt content on marshall characteristics in AC-BC samples. The method used is laboratory study with Marshall test equipment. The test was done with 24 hours fresh water immersion and waterbath 60 oC for 30 minutes. The results after Kao reflect a direct proportion of freedom relative to the addition of resin sap, which is 1663 kg; 1914 kg; 1961 kg and 2040 kg. Similarly, the VFA (67,046; 68,251; 73,115 and 74,397) and the marshall quota (457; 590; 589 and 658). In contrast to stability, the actual VMA is inversely proportional (5,766; 15,530; 14,642 and 14,43) and the melt is changed parabolically (3.64 mm; 3.83 mm; 3.33 mm and 3.10 mm) and the VIM b is unstable (3,828; 4,201; 3,741 and 3,911) respectively. These conditions make it possible to get the right price to compare AC-BC, and the optimal percentage at the time of resin of 3.5%